Transcendental deduction and realism in the Critique of Pure Reason (Cadernos de Filosofia Alemã: Crítica e Modernidade, 2023)
The article addresses the merits of the Transcendental Deduction, a central argument for the Critique of Pure Reason, with regard specifically to the clash with Hume's epistemological skepticism. The idea is developed that the price paid by Kant in his anti-Humean project, the transcendental idealist position, although conceptually distinct from Berkeley's idealism and, in fact, the consequent development of a more general modern anti-realism, is still and precisely because of this common commitment in a territory that is unavoidably vulnerable to the critique of knowledge, hence the presence of a dogmatic foundation implicit in this point of Kant's work.